2010
DOI: 10.1590/s0104-12902010000100013
|View full text |Cite
|
Sign up to set email alerts
|

A estratégia saúde da família: motivação, preparo e trabalho segundo médicos que atuam em três distritos do município de Duque de Caxias, Rio de Janeiro, Brasil

Abstract: Analisou-se como o médico do Programa de Saúde da Família (PSF) de Duque de Caxias percebe sua atuação. Foram feitas entrevistas semiestruturadas com 15 médicos que trabalham no primeiro, terceiro e quarto distritos, sendo o primeiro urbano e os demais rurais. Aplicou-se aos dados a análise de conteúdo, na modalidade temática. Os núcleos de sentidos referiram-se à motivação e ao preparo para ingressar na equipe, e a oportunidade que o PSF oferece para estabelecer vínculos com o paciente, reforçando o acolhimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
3
0
3
Order By: Relevance
“…As social control, it is understood the capacity and the possibility that the organized society has to intervene effectively in the definition and implementation of the UHS management model and the health care model for the execution of public policies. 22 Social participation for local development and organization becomes essential. The research identified positive and negative reports regarding the use of the collegiate instrument manager.…”
Section: Discussionmentioning
confidence: 99%
“…As social control, it is understood the capacity and the possibility that the organized society has to intervene effectively in the definition and implementation of the UHS management model and the health care model for the execution of public policies. 22 Social participation for local development and organization becomes essential. The research identified positive and negative reports regarding the use of the collegiate instrument manager.…”
Section: Discussionmentioning
confidence: 99%
“…Training programs should develop attractive methodological strategies, as a study in the city of Duque de Caxias-RJ showed that FHS professionals did not feel motivated to participate in training, alleging that these programs did not add to the professional experience and that they were eminently theoretical. 32 There is a consensus regarding the need for the periodic training of professionals, 26 to prevent improper conduct in attending the population. It is therefore necessary that attractive strategies are recognized as essential for the development of care activities and valued by the FHS professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Após as intervenções, o percentual de encaminhamentos de paciente com rolha de cerume para a Atenção Secundária permaneceu semelhante. Confirma-se, pois, que, para aumentar a eficiência do médico de família em procedimentos que dependem de semiotécnica específica, o treinamento em serviço é fundamental 8 .…”
Section: Discussionunclassified